Prevalence of substance use disorders among patients with systemic lupus erythematous and major depressive disorder - Kevin J. Varghese; Alexandra Dellenbaugh; Fei Cao; Douglas M. Burgess; Xiaofeng Yan (Wiley, 2023)
Abstract Background Major depressive disorder (MDD) has a higher prevalence among patients with systemic lupus erythematous (SLE). Patients with SLE struggle with stressors such as social stigma and reduced employment. Furthermore, substance use disorders (SUD) are strongly associated with MDD. Objectives This research investigated whether comorbid MDD among patients with SLE is associated with an increased prevalence of SUD diagnoses. Rates of various SUD diagnoses were compared among patients with SLE. Methods This was a retrospective comparison study of the medical record. All data were extracted from I2B2, a deidentified dataset from an academic hospital in an urban setting. Upon stratifying patients with SLE into two groups with or without MDD, chi‐squared test comparing SUD was completed. An additional analysis stratified patients with MDD into two groups with or without comorbid SLE and completed the chi‐squared test to compare SUD. Results Patients with SLE and comorbid MDD were more likely to have diagnoses of tobacco, alcohol, and opioid disorders, among others. The most common SUD was tobacco (prevalence 59.94%). Furthermore, the diagnosis of SLE among patients with MDD was not associated with increased rates of SUD diagnosis. However, patients diagnosed with comorbid SLE and MDD were more likely to have tobacco use and opioid use disorder diagnosis. Conclusions This study demonstrates a consistently higher rate of SUD diagnoses among patients diagnosed with SLE and comorbid MDD versus SLE alone. Rates of both tobacco and opioid use disorder were higher among patients with MDD and comorbid SLE when compared to MDD alone. Our study is limited by its retrospective analysis and does not include an analysis of the treatment of comorbid depression on SUD. For clinicians who take care of patients with SLE, when they have comorbid MDD, SUD should be screened.